Research of the implementation of modern wireless broadband electronic communication services - Pasarelska, Teodora (Yearbook Telecommunications, 2024)
The article aims to analyze various aspects of the implementation of modern wireless broadband electronic communication services, focusing on spectrum management, regulatory framework and technological innovations. The processes of licensing and allocation of radio frequency spectrum are studied as important factors for the successful provision of broadband services. The main contribution of the article is to clarify the role of public-private partnerships in the development of these services and to propose strategies for improving the infrastructure and organizational part of the implementation. The article also examines the integration of new technologies such as 5G and IoT, which offer new opportunities for the development and expansion of wireless networks. An analysis is made of operational management and the factors that determine the effectiveness of the implementation. The results of the study offer useful recommendations for improving the processes related to the implementation of modern wireless broadband services and emphasize the importance of innovation and strategic planning to achieve long-term results.